2014
DOI: 10.1017/s0144686x1400004x
|View full text |Cite
|
Sign up to set email alerts
|

The representation of older people in television advertisements and social change: the case of Japan

Abstract: The representation of social groups in advertising has been a major concern in academia. However, research focusing on older people has been scant and mainly conducted in Western countries. In Japan, the country that has been most affected by demographic change, this research area has received little attention. Through a content analysis of a systematic sample of 2,972 television advertisements broadcast on the five major commercial television stations in Japan in 1997 and 2007, this paper tries to fill this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 46 publications
4
33
0
5
Order By: Relevance
“…The same pattern of under-representation has also been observed in relatively recent studies (Prieler et al, 2015;Kay & Furnham 2013;Furnham & Paltzer, 2010), especially older females being absent from mainstream advertising, compared to senior males. The worldwide magnitude of the standardized portrayal of seniors in advertising -mainly younger than their chronological age; as grandfather/grandmother, as housewife or as consumer of health services -has proved to be at higher level since the phenomenon have been reported in many cultural areas: in the USA (Miller et al, 2004), UK (Williams, Ylänne, Wadleigh & Cheng, 2010), Germany (Zhang et al, 2006), Malaysia and South Korea (Ong & Chang, 2009), Australia (Higgs & Milner, 2005), Japan (Prieler et al, 2015), India (Harwood & Roy, 1999), Hong Kong, South Africa and New Zealand (Furnham & Paltzer, 2010). Intercultural data have also revealed that young women tend to be twice more distributed in commercials than older ones (in Austria, Turkey, Poland, Sweden and Bulgaria), while in Russia and Serbia, neither a woman, nor a man aged 55+ appears in commercials.…”
Section: Advertising Models For Silver Consumerssupporting
confidence: 79%
See 2 more Smart Citations
“…The same pattern of under-representation has also been observed in relatively recent studies (Prieler et al, 2015;Kay & Furnham 2013;Furnham & Paltzer, 2010), especially older females being absent from mainstream advertising, compared to senior males. The worldwide magnitude of the standardized portrayal of seniors in advertising -mainly younger than their chronological age; as grandfather/grandmother, as housewife or as consumer of health services -has proved to be at higher level since the phenomenon have been reported in many cultural areas: in the USA (Miller et al, 2004), UK (Williams, Ylänne, Wadleigh & Cheng, 2010), Germany (Zhang et al, 2006), Malaysia and South Korea (Ong & Chang, 2009), Australia (Higgs & Milner, 2005), Japan (Prieler et al, 2015), India (Harwood & Roy, 1999), Hong Kong, South Africa and New Zealand (Furnham & Paltzer, 2010). Intercultural data have also revealed that young women tend to be twice more distributed in commercials than older ones (in Austria, Turkey, Poland, Sweden and Bulgaria), while in Russia and Serbia, neither a woman, nor a man aged 55+ appears in commercials.…”
Section: Advertising Models For Silver Consumerssupporting
confidence: 79%
“…Since the early 90s and onwards, the reasons for the limited presence of seniors in advertising has been largely investigated in marketing studies (Ong, Kitchen & Jama;2008;Carrigan & Szmigin, 1999;Greco 1988), consumer psychology Guido & Amatuli, 2014), advertising research (Prieler et al, 2015;Panic, Cauberghe & Verhoye, 2011) and sociology of ageing (Gilleard & Higgs, 2011;Settersten & Angel, 2011;Wassel, 2011). There is much empirical data to argue that, in general, seniors preferred to be depicted ten years younger than their real chronological age (Yoon & Powell, 2012, p. 1324Prieler et al, 2011, p. 244;Robinson et al, 2008, p. 236).…”
Section: Advertising Models For Silver Consumersmentioning
confidence: 99%
See 1 more Smart Citation
“…Összehasonlításul, Prieler és szerzőtársai (2015) japán mintájában 70% volt a főszereplők aránya, Chen (2014) brit és tajvani mintájában 36,1% illetve 43,3%. Bár nyilvánvaló a kulturális különbség is, a szerepkörök minősége utalhat az adott generáció tiszteletére is az adott társadalomban (Prieler et al 2015).…”
Section: áBraunclassified
“…Yet, despite the importance of Baby Boomers, marketing's focus on youth and neglect of older adults is well documented (Niemela-Nyrhinen, 2007;Thompson and Thompson, 2009). Even with their relatively large share of spending, Nielsen (2012) estimates that less than 10% of advertising is geared towards them, an assertion supported by advertising content analyses across different media and nations (Kessler et al, 2009;Prieler et al, 2011Prieler et al, , 2014Simcock and Sudbury, 2006).…”
Section: Aging Consumersmentioning
confidence: 99%